2022
DOI: 10.1021/acs.jafc.1c07480
|View full text |Cite
|
Sign up to set email alerts
|

Risk to Public Health Regarding Doxycycline Residues in Chicken Claws

Abstract: Doxycycline residues in claws may pose a potential risk to humans. A study with broiler chickens was performed to find the concentrations of doxycycline in claws after treatment. For the quantification of the antibiotic of interest in claws, an ultrahigh-performance liquid chromatography–tandem mass spectrometry method was developed. Doxycycline was detectable at 3043 μg/kg at sub-therapeutic treatment, 223 μg/kg after therapeutic doses, and 14 μg/kg after spray application on the last day of the experiment (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…The Commission of the European Communities Regulation (EC) No. 1096/2009 classifies animal by‐products into three categories according to the level of risk to the public and animal health (Gajda et al, 2022). Chicken claw belongs to category three (low risk), which is considered fit for processing for human consumption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Commission of the European Communities Regulation (EC) No. 1096/2009 classifies animal by‐products into three categories according to the level of risk to the public and animal health (Gajda et al, 2022). Chicken claw belongs to category three (low risk), which is considered fit for processing for human consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Chicken claw, a byproduct of the poultry industry, is a common and popular food resource in some countries and regions of Asia and Africa (Gajda, Szymanek‐Bany, Nowacka‐Kozak, & Gbylik‐Sikorska, 2022). China is the main importer of chicken claw in the world (Santos et al, 2011), and chicken claw has recently been made into ready‐to‐eat products for sale in the Chinese market, such as sauce braised chicken claw.…”
Section: Introductionmentioning
confidence: 99%
“…Among these studies, doxycycline was found at the highest concentrations and with the longest persistence times in feathers and claws. The concentration of doxycycline in feathers one day after treatment was 1,050 ± 596 μg/kg, while in claws, doxycycline was found at the level of 6,370 ± 922 μg/kg ( 19 , 20 ). In the present research, the determined concentration of doxycycline in bones was 5,840 ± 843 μg/kg one day after ceasing treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Some publications reported the depletion and persistence of oxytetracycline and doxycycline in feathers ( 9 , 19 ). Others presented the bioaccumulation of oxytetracycline, florfenicol and doxycycline in chicken claws ( 8 , 20 , 33 ). Among these studies, doxycycline was found at the highest concentrations and with the longest persistence times in feathers and claws.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation